94 Genetic basis of blood traits in beef cattle and their relationship to production traits at weaning. (30th November 2020) - Chinchilla-Vargas, Josue; Kramer, Luke; Lester, Toby D; Lester, Toby D; Backes, Elizabeth A; Anschutz, Karen; Decker, Jared E; Stalder, Kenneth J; Rothschild, Max F; Koltes, James E
Abstract: Disease represents one of the main factors that determine profitability in animal production. Previous research has observed significant correlations between blood cell counts and the animal's health status. We hypothesize that blood cell traits may be an effective indicator of performance in beef cattle. Complete blood counts were recorded from approximately 500 crossbred animals at weaning (Angus background crossed with Hereford, Charolais, Sim-Angus, Brangus) born between 2015 and 2016 and raised on toxic or novel tall fescue on three different farms. The animals were genotyped at an approximate density of 50, 000 SNPs and the genotypes were imputed to an approximate density of 200, 000 SNPs. Heritability, genetic and phenotypic correlations were estimated for 15 blood and 4 production traits across and within environments. Finally, with the objective of identifying the genetic basis underlying the different blood traits, a genome wide association study (GWAS) was performed for all traits. Heritability estimates ranged from 0.11 to 0.60, and generally weak phenotypic correlations and strong genetic correlations were found, however these parameters varied across environments, pointing to GxE interactions. GWAS identified 90 1 Mb windows that explained 0.5% or more of the estimated genetic variance for at least 1 trait with 21 windows overlapping two or more traits. Further research efforts include identifying underlying candidate genes for traits and comparing toxic and novel fescue effects on blood traits. It appears that blood traits have weak phenotypic correlations but strong genetic correlations among themselves, as evidenced by important overlapping regions of genetic control for similar blood traits. However, blood traits have limited potential as indicator traits for productivity.